The Inclusivity of Zakat as an Instrument of Social Justice in the Modern Era:: A Reconstruction of Islamic Law Concerning Non-Muslim Zakat Beneficiaries - Abdul Hakim; Pipip Ahmad Rifa'i Hasan (Divisi Penelitian dan Pengabdian Masyarakat Yayasan Cerdas Pedia Indonesia, 2026)
The contemporary global order confronts structural inequality crises demanding macro distributive justice interventions. Zakat serves as a potent fiscal redistribution instrument, yet classical fiqh's exclusivity, restricting beneficiaries strictly to Muslims, triggers socio-religious tension within the governance of pluralistic modern nation-states. Precedent literature remains predominantly trapped in the dichotomy of literalist dogmatic compliance and empirical SDG metrics without addressing fundamental jurisprudential reconstruction. This article aims to epistemologically reconstruct the theological boundaries of zakat beneficiaries (mustahiq) through the analytical framework of contemporary maqashid syariah. Results demonstrate that expanding the mu'allafah qulubuhum and fi sabilillah categories to vulnerable non-Muslim populations is legally legitimized to protect human survival and social cohesion. This research's novelty integrates Western distributive justice theories with classical normative text reinterpretations under the framework of Islamic cosmopolitanism. Consequently, state amil authorities can legitimize zakat as public cross-identity social finance to demolish demographic exclusion and accelerate global SDG targets comprehensively and equitably.